Projetos integradores no IFRN: reflexões sobre os documentos norteadores e o contexto da prática no Campus Mossoró - Santos, Luiz Antonio da Silva dos (2018)
The present work is part of the research line of Human and Social Sciences Teaching (POSENSINO) and seeks to present an analysis on the Integrative Projects at the IFRN, Mossoró Campus. In this way, we try to answer the following problem: how the Integrative Projects are conceived, planned and developed in the Technical Course of Middle Level Integrated in Informatics in this institution of Professional Education. In order to answer such questioning, we are guided by the theoretical-analytical framework formulated by Ball, Maguire and Braun (2016), seeking the relation of these projects with the institutional documents of the IFRN and the understanding of the configurations of how their production process takes place in the context of practice, based on the principles of Interdisciplinarity. The chosen approach considers a continuous cycle constituted by three main contexts: the context of influence, in which the decisions and the diverse political discourses are initiated and / or constructed; the context of the production of text, in which texts with the political definitions are produced; and the context of practice, in which curricular definitions are recreated and reinterpreted. Research is characterized as qualitative and exploratory research. The methodological procedures of the investigation included a theoretical-methodological matrix composed of several instruments, namely: literature review, documentary analysis, open interviews and application of questionnaires. During the fieldwork period, we collected primary data, through interviews with three servers that worked on the Integrator Project and through semi-structured questionnaires with 24 students. The content analysis of the data presented in the institutional documents revealed that the IFRN's Political-Pedagogical Project presents texts with hybrid meanings, since it affirms that the Integrating Projects can be developed in a disciplinary or interdisciplinary way. Thus, the divergent discourse adopted in the PPP shows that it, like any other document, is subject to the interests, disputes and negotiations of the disciplinary communities. The hybrid senses found express this possible negotiation, distancing itself from what is understood as integrating character of the proposal. The work also verified that the way in which the Integrator Project has been produced shows significant distances with respect to the IFRN institutional documents. We also noticed that the Integrator Project in the Technical Course of Integrated Higher Level in Informatics, when developed, did not yet allow an articulation of the curricular components nor the articulation of the knowledge of the general formation with the knowledge of the technical formation, and, therefore, was able to produce differentiated effects for the students, thus expressing that the subjects of the school recreate and reinterpret what is placed to them. The study recognizes that the difficulties of the IFRN in the implementation of this interdisciplinary proposal do not eliminate the commitment of the Institute to promote an interdisciplinary approach that puts in a relational and global perspective technical areas and areas of general formation. We believe, however, that there is a need to reformulate the proposal for the implementation of the integrating project, since such difficulties can lead to losses in the development of a comprehensive and interdisciplinary training, as advocated in the IFRN guiding documents